Beyond the Lab - Umbrello, Steven (2024)
Carne Coltivata: Etica dell’agricoltura cellulare by Luca Lo Sapio critically explores the ethical, environmental, and cultural ramifications of cellular agriculture, particularly cultivated meat. Through a philosophical lens, Lo Sapio evaluates the potential of this technology to address ethical concerns tied to traditional meat production, such as animal welfare, environmental sustainability, and health implications. However, the book also critiques the potential cultural and ecological consequences of detaching meat production from traditional agricultural practices. Lo Sapio's discourse navigates the complex interplay between technological progress and the intrinsic value of natural life processes, urging a balanced consideration of cultivated meat's implications on global food cultures, food sovereignty, and the sanctity of life.